Your Physical Activity Is in Your Hand—Objective Activity Tracking Among University Students in Hungary, One of the Most Obese Countries in Europe - Ráthonyi, Gergely; Takács, Viktor; Szilágyi, Róbert; Bácsné Bába, Éva; Müller, Anetta; Bács, Zoltán; Harangi-Rákos, Mónika; Balogh, László; Ráthonyi-Odor, Kinga (Frontiers in Public Health, 2021)
Inadequate physical activity is currently one of the leading risk factors for mortality worldwide. University students are a high-risk group in terms of rates of obesity and lack of physical activity. In recent years, activity trackers have become increasingly popular for measuring physical activity and have the potential to alter user’s physical activity behavior. The aim of the present study is to examine whether university students in Hungary meet the health recommendations for physical activity and investigate the impact of different variables (semester-exam period, days-weekdays, days, months, sex) on the level of physical activity in free-living conditions for three months period. In free-living conditions, 57 healthy university students (male: 25 female: 32 mean age: 19.50 SD=1.58) wore MiBand activity tracker for three months. Independent sample t-tests were used to explore differences between sexes. A One-way analysis of variance (ANOVA) was used to explore differences in measures among different grouping variables and step count. A Two-way ANOVA was conducted to test for differences in the number of steps by days of the week, months, seasons and for sex differences. Tukey HSD post-hoc tests were used to examine significant differences Students in the study achieved 10,000 steps per day on 17% of days (minimum: 0%; maximum: 76.5%; median: 11.1%). Unfortunately, 70% of the participants did not comply the 10,000 steps at least 80% of the days studied. No statistical difference were found between sexes. However, significant differences were found between BMI categories, the number of steps in the overweight category was significantly lower (F=72.073 p=0.000). The average daily steps were significantly higher in autumn (t=11.457 p=0.000) than in winter. During exam period average steps/day significantly lower than during fall semester (t=13.696 p = 0.000). On weekdays, data were significantly higher than on weekends (F=14.017 p=0.000), and even within this, the greatest physical activity can be done by the middle of the week. Our data suggest that university students may be priority groups for future physical activity interventions. Commercial activity trackers provide huge amount of data for relatively low cost therefore it has the potential to objectively analyze physical activity and plan interventions.